Mecanismos discursivos e a representação da feminilidade e espiritualidade em artigos da Revista Claudia - Trindade, Kelly Alessandra (2007)
In the present paper we will analyze the discursive mechanisms found in spirituality related texts published in Revista Claudia, with special interest in their relationship with the behavioral paradigm of the modern women. The ideology propagated by the media discourse is disseminated in diverse social groups, establishing values for evaluation of the reality and influencing social behavior. The analyses performed aimed to demystify the language that supposedly has no intentionality and to observe the confrontation between this language and the individual, its history and ideology. It will be possible to conclude that ingenuous texts or non influent authorship did not exist. In this paper it is elucidated, by means of a theoretical procedure of the Discourse Analysis, that the language plays an important role as vehicle of thought expression and values of a determined time